2020
DOI: 10.1186/s40510-019-0302-0
|View full text |Cite
|
Sign up to set email alerts
|

The informative value and design of orthodontic practice websites in The Netherlands

Abstract: Background: The aims of this cross-sectional study were to investigate the regulatory compliance of Dutch practice websites offering orthodontic services, readability of the available treatment information, website design as well as possible relationship with practice location and professional qualification of practitioners. Methods: A comprehensive Internet search was performed using the Google search engine and five relevant terms in Dutch. Eligibility screening of the first 50 results of each search led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…The mean BDC scores of websites of all authorships were higher than those reported by Oey and Livas for orthodontic practice websites in the Netherlands [36], reflecting better optimization of the websites evaluated in our study. Professional organization websites had the highest mean BDC score, followed by multidisciplinary dental clinics (Table 2).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The mean BDC scores of websites of all authorships were higher than those reported by Oey and Livas for orthodontic practice websites in the Netherlands [36], reflecting better optimization of the websites evaluated in our study. Professional organization websites had the highest mean BDC score, followed by multidisciplinary dental clinics (Table 2).…”
Section: Discussioncontrasting
confidence: 64%
“…The financial backup and enhanced office functions of professional organizations may therefore explain this result. Similarly, consolidation of dental care by multidisciplinary dental clinics and dental practice chains may have enabled better integration of information technology services for multidisciplinary dental clinics [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research into the design and content of orthodontic practice websites in the UK revealed wide variation amongst websites and suboptimal performance against validated measures of accessibility, usability and reliability [11]. This echoes results of a recent Dutch study which found that the informative value and design of orthodontic practice websites in The Netherlands was low and information was set above the average reading age of the population [16]. As we move forward, even as we possibly exit the disruption of COVID-19, It would be encouraging to see patients able to access relevant and reliable information from the website or social media page(s) of the practice they attend.…”
Section: Facebook Identified 62mentioning
confidence: 88%
“…The study found that despite the apparent variability in the quality of information on the Internet, the overall quality rating, as measured by the DISCERN tool, tends to be low or medium for the majority of websites. Oey and Livas [ 35 ] assessed hundred websites, employing the Dutch language as the search language. The mean FRES derived from the examination of information presented on websites within the study presented textual content characterized by a level of complexity, indicating difficulty in understanding.Research conducted in diverse linguistic contexts analogous to the present study has revealed parallels with our findings.…”
Section: Discussionmentioning
confidence: 99%